AN EXAMINATION OF THE IMPACT OF FAKE NEWS ON GOVERNANCE IN NIGERIA - Oji, Okechukwu Richard; Tsala, Thakuma (SOUTH EAST JOURNAL OF POLITICAL SCIENCE, 2021)
The issue of fake news and its impact on the society has become very prominent in recent years. Despite the fact that fake news is not a new phenomenon, technological advances have constructed a fertile environment for fake news to spread rapidly. The Paper avers that social media platforms, such as Facebook, Twitter or YouTube, offer grounds for generation and distribution of fake news. Accordingly, the Public, development practitioners and other stakeholders around the world have raised concerns about the persistent occurrence of misinformation in contemporary politics mainly because of its character and manifestations. The fact that misinformation can swiftly spread unverified, has gained global notoriety and its threat to democracy re-emphasizes the need for corrective measures.